The expression of steroidogenic genes in ovine corpus luteum during early pregnancy - Mustafa Hitit; Mehmet Köse; Bülent Bülbül; Nadir Koçak; Mehmet Osman Atlı (Eurasian Journal of Veterinary Sciences)
Aim: The goal of this study was to investigate the expression of steroidogenic genes in ovine corpus luteum during early pregnancy. Materials and Methods: The animal model was designed as pregnancy; ewes were divided into three sub-groups, pregnancy 12th day: P12, pregnancy 16th day: P16, pregnancy 22th day: P22, and cyclic day 16 (C16). The expression of steroidogenic genes (steroidogenic acute regulatory protein; StAR, cytochrome P450 side-chain cleavage; P450sscc, and 3b-hydroxysteroid dehydrogenase/ delta5 delta4-isomerase; 3?HSD) was evaluated using qPCR, and mRNA localization of StAR was detected on P16 against C16 through in-situ hybridization. Results: The expression of StAR mRNA was higher on day P22 and P16 compared to P12 (p<0.05), while it was at a steady-state level on day P22 vs P16 (p>0,05). mRNA expression of P450scc was greater on day P22 and P16 than day P12 (p<0.05), however on day P22 vs P16, it was at a steady-state level (p>0,05). Also, mRNA expression of 3?HSD had a similar trend; it was higher on day P22 and P16 compared to P12 (p<0.05), while it was at a steady-state level on day P22 vs P16 (p>0,05). In in-situ hybridization, we did not detect StAR mRNA on cyclic day 16 (C16) while abundantly expressed in luteal cells in P16. Conclusion: The mRNA expression of steroidogenic genes may appear to play a critical role during early pregnancy in ewes. Accordingly, it can be suggested that the steroidogenic pathway in the corpus luteum of ewe may transcriptionally regulate progesterone synthesis required for maintenance of early pregnancy.